The experience in treating nephroblastoma at Hue Central Hospital - Ho, Huu Thien; Pham, Nhu Hiep; Pham, Anh Vu; Mai, Trung Hieu; Phan, Hai Thanh; Nguyen, Thanh Xuan; Van, Tien Nhan; Tran, Nghiem Trung; Pham , Trung Vy; Tran, Si Doan Diem; và c.s. (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2016)
The experience in treating nephroblastoma at Hue Central Hospital Objective: Evaluation of effectiveness of surgical treatment combined with chemo-radio therapy of nephroblastoma. Material and methods: Prospective collected data from 25 patients with nephroblastoma who underwent surgical treatment combined with chemo-radio therapy at Hue Central Hospital from January 2010 to January 2016. Result: Age average 42.3 months, male/female 1.27/1, the most common symptom was abdominal mass with 96%, in 64% of the cases the tumor occured on the right side, in 36% on the left side. 72% of the patients were treated with National Wilms Tumor Study Protocol, 28% of the patients were treated with International Society of Paediatric Oncology Protocol. Average operating time was 120±25 minutes. The duration of hospitalization was 6.2±0.3 days. 28% of the patients were pathologically diagnosed with favorable histology, 56% with intermediate histological and 16% of the patients with unfavorable histology. Recurrence rate was 12% in the first year, death rate 8%. Survival rate after 2 years was 92%. Conclusion: Surgical treatment combined with chemo-radio therapy of nephroblastoma is safe and effective.